Development of manufacturing techniques for Ti-based functionally graded coatings / Reza Mahmoodian - Reza, Mahmoodian (2013)
Coating techniques are commonly used in the ceramic-lined piping industries. However, the obtained ceramic layers are too brittle and fail under piping processes such as branching and making orifices. This is in consequence to improper manufacturing techniques, which do not guarantee functionally graded coatings or the local reinforcement of coatings. Therefore, to overcome such setbacks, the current research focuses on the development of manufacturing techniques for in-situ, locally reinforced composites with good mechanical properties. Various manufacturing techniques for the fabrication of ceramic and composite coatings have been proposed, designed, and implemented. Titanium carbide, silicon carbide, and alumina composite phases were processed under different manufacturing conditions. The developed centrifugal self-propagating high-temperature synthesis (SHS) technique helped to fabricate an in-situ titanium carbide-alumina-iron composite with several intermetallic phases successfully. The SHS reaction under centrifugal force design was such as to combine with a chain reaction between titanium and carbon elemental powders. The developed centrifugal-assisted thermite method served to fabricate ceramic products in embedded and offset specimen positions. The elemental powders of titanium (Ti), carbon (C), and silicon (Si) were ball-milled and compacted into pellets, then exposed to a massive amount of heat generated from the thermite reaction of Fe2O3 and Al in a steel tube mounted in the developed centrifugal accelerator machine. The result was the formation of titanium carbide (TiC) and Al2O3-Fe composites. Evidently, the centrifugal force facilitated the formation of multi-component products and particle segregation during the process. In addition, centrifugal acceleration had a significant effect on both metallurgical alloying and mechanical interlocking between different sample layers when forming in-situ functionally graded coating with enhanced hardness and good fracture toughness. Processing silicon carbide (SiC)-based composite coating was not feasible, unlike the successful formation of TiC. A ceramic-coated pipe was produced using a conventional centrifugal thermite process. Consequently, the effects of an unexpected phase formed at the pipe’s head on the joining and post-processing of the ceramic-lined composite pipe with Al2O3 and Fe layers were studied. A plasma-assisted processing method was developed to fabricate ceramic parts and pellets under normal gravity and centrifugal force. Plasma-assisted reactions under normal gravity were successfully applied to fabricate SiC with large crystals of 270 μm and TiC with a highly crystallized super hard phase of 3660 HV hardness. The analytical and modified smoothed particle hydrodynamic (MSPH) computational technique simulated the molten particles’ motion on multi-scale analysis levels. The radial velocity and radial velocity gradient of molten alumina and iron infiltration inside the TiC product along with viscosity rate variations during the coating process were also simulated. The obtained results and conclusions are ultimately discussed, after which suggestions for future work are proposed.